Automated head-fixation training system with high levels of animal participation in psychoacoustic tasks - Ji Liu; Kate Maximov; Patrick O. Kanold (PLoS ONE, 2025)
Many animal training paradigms rely on head-fixation. Head-fixation training is typically laborious and can benefit from automation to relieve the workload and reduce the variability in the training outcome. Several groups have reported successful implementations of such systems, but throughput varied greatly across groups. In addition, most studies relied on brief periods of head-fixation sessions (≤ 1 minute) to reduce the potential stress on the animal. Here, we report the design of a new system that could achieve head-fixation sessions on the order of minutes with a high participation rate from the animal (100%). Throughout the training period, each mouse performed a total of close to 40 minutes of head-fixation training on average each day and learned common psychoacoustic tasks, i.e., tone detection and tone discrimination. Our system can achieve highly efficient training with minimum idling time, allowing combinations with high-end neural recording equipment to achieve maximum training and data collection efficiency.